Approximate Formulas for the Determination of the Carrying Capacity of Ice (Priblizhennye Formuly dlya Opredeleniya Nesushchei Sposobnosti Lda) - Panfilov,D. F. (1972)
A rigorous calculation of the carrying of capacity of ice is based on the theory of elastic foundation. However, experiments showed that for the case of the movement of loads over ice this theory characterizes the deformation of an ice layer inexactely, and only with some degree of approximation. At the same time it is quite complicated and requires that cumbersome calculations be performed. In the report, based on theoretical and experimental studies, simple and quite accurate formulas are derived for the determination of the carrying capacity of ice. Trans. of Trudy Koordinatsionnykh Soveshchanii po Gidrotekhnike (USSR) n10 1964.